Heart rate monitoring improves clinical assessment during 6-min walk. (December 2020) - Lachant, Daniel J.; Light, Allison; Offen, Melissa; Adams, Jamie; White, R. James
Right ventricular (RV) function is a predictor of outcomes in pulmonary arterial hypertension (PAH). The 6-min walk test (6MWT) is likely an indirect measure of RV function during exercise, but changes in absolute walk distance can also be influenced by factors like effort and musculoskeletal disease. Paired 6MWT with continuous electrocardiogram monitoring was performed in stable PAH patients, patients adding PAH therapies, and healthy controls. Heart rate expenditure (HRE) was calculated (integrating pulse during 6MWT) and then divided by walk distance (HRE/d). We also evaluated changes in peak heart rate, time above age-adjusted maximum predicted heart rate, and heart rate at 6 min. HRE/d was compared to invasive hemodynamic measures in patients who had right heart catheterization performed within seven days, WHO functional class assessment, and Emphasis 10 questionnaire. We measured two 6MWT in 15 stable PAH patients, 13 treatment intensification patients, and 8 healthy controls. HRE/d was reproducible in the stable PAH group (median difference, −0.79%), while it decreased (median difference, 23%, p = 0.0001) after adding vasodilator therapy. In 11 patients with right heart catheterization, HRE/d correlated strongly with stroke volume, r  = −0.72, p  = 0.01. Peak heart rate decreased after adding vasodilator therapy. HRE/d also correlated with WHO functional class and Emphasis 10 score. Continuous heart rate monitoring during 6MWT provides valuable physiologic data accounting for effort. HRE/d appears to enhance test reproducibility in stable patients while detecting change after adding therapy as compared to walk distance alone.